A structural model assessing key factors affecting women's entrepreneurial success: Evidence from India. Issue 1 (2nd November 2018) - Chatterjee, Namrata; Das, Niladri; Srivastava, Nishit Kumar
Abstract : Purpose: The present study aims to investigate the influence of key factors on the success of women micro-entrepreneurs in select states of India. Design/methodology/approach: An empirical study is carried out to understand the influence of the psychological, socio-cultural, skill and resource-related factors on the success of women entrepreneurs. To achieve the set goal, a comprehensive questionnaire is developed for collecting data and is analyzed using the t -test, the chi-square test and structural equation modeling. Findings: The proposed model is validated using structural equation modeling, and the fitness values indicate that the model is fit to explain the entrepreneurial success of women entrepreneurs in India. Practical implications: The result advocates that the participation of women entrepreneurs may be increased to not only improve national growth but also empower women in India. Originality/value: In the context of the women micro-entrepreneurs, no such study covering such a vast area of India has been carried out.